State accountability and legal responsiveness in preventing diabetes mellitus from an early age: Between moving towards a golden Indonesia or an anxious Indonesia - Pasaribu, Yusuf Yefta; Antony, Antony (Institute of Computer Science (IOCS), 2024)
Until now, diabetes mellitus not only attacks adults but also attacks children as the nation's next generation. This is of particular concern if it is related to the drastic increase in the number of diabetes mellitus sufferers in Indonesia. Apart from Indonesia, there are also several other countries that are fighting high rates of diabetes mellitus, such as China, Singapore, England and other countries. The high rate of diabetes mellitus in society is caused by inaccurate information on the contents of a product, there are terms that are difficult for consumers to understand, nutritional information that is not open/hides negative facts about the content in the product and low public awareness in paying attention to the composition of the nutritional value of food products and drink to be consumed. So that legal protection and responsiveness have not yet been maximally realized for the public as consumers. This research aims to examine the accountability and responsiveness of law in Indonesia in preventing diabetes mellitus from an early age by conducting a comparative study between countries that have been effective in reducing diabetes mellitus rates. The research method used is a doctrinal normative legal research method with a statutory regulation approach, a conceptual approach and a comparative approach. The results of this research show that there are effective strategies in preventing diabetes mellitus, namely updating nutritional value information labels and implementing excise taxes on the food and sweetened beverage industry. Adopting these strategies is a form of revolution and a form of legal responsiveness in improving the level of national health towards a Golden Indonesia.